1972
DOI: 10.1042/cs0430533
|View full text |Cite
|
Sign up to set email alerts
|

An Organ Culture Study of the Effect of Drugs on the Secretory Activity of the Human Bronchial Submucosal Gland

Abstract: S U M M A R Y1. The incorporation of tritiated glucose into bronchial gland cells enables their glycoprotein secretion to be followed by radioautography. The number of cells from which secretion is observed after 4 h of cell culture is the secretory index.2. Large variations in secretory index were observed between the bronchi of different subjects, but the secretory index was proportional to gland size.3. The secretory index was increased by parasympathomimetic drugs and diminished by parasympatholytic drugs,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
64
0

Year Published

1978
1978
1985
1985

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(68 citation statements)
references
References 3 publications
4
64
0
Order By: Relevance
“…The RIA would therefore be applicable to intestinal biopsies or organ cultures. Because we have until this time had to rely mainly upon morphological examination of goblet cells to identify conditions of goblet cell hyperplasia or depletion (34,35), the RIA may be useful in adding precision to studies of mucus in human disease.…”
Section: Resultsmentioning
confidence: 99%
“…The RIA would therefore be applicable to intestinal biopsies or organ cultures. Because we have until this time had to rely mainly upon morphological examination of goblet cells to identify conditions of goblet cell hyperplasia or depletion (34,35), the RIA may be useful in adding precision to studies of mucus in human disease.…”
Section: Resultsmentioning
confidence: 99%
“…Animals that have recently had respiratory tract infections display mucous gland hypertrophy (Jones, Baskerville & Reid, 1975), and human bronchi with hypertrophied glands have different sensitivities to acetylcholine stimulation and atropine block (Sturgess & Reid, 1972). It is likely that hypertrophied glands undergo a change in the nature or number of end-organ receptors, and that this alters their response to neurotransmitters.…”
Section: Discussionmentioning
confidence: 99%
“…Submucous glands are richly innervated with parasympathetic fibers (20). Other studies, including several of human lung airways in vitro (7,8), have demonstrated that parasympathetic stimulation increases mucous glycoprotein secretion. The cholinergic agonist, methacholine (100 /.M), added in period II caused a 62% increase (n = 10,P < 0.001) above control (Fig.…”
Section: Introductionmentioning
confidence: 99%